State Bar Annual Meeting at Town and Country Hotel San Diego - Watkins, Howard::::::::: (1985)
Fresno County Bar Association delegates at Conference of Delegates: Mary Louise Frampton, Herbert Levy, Brad Geery, Leonard Zins, William J. Smith, Howard Zidenberg and Judy Soley